1987
DOI: 10.1002/hep.1840070302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapeutic paracentesis on systemic and hepatic hemodynamics and on renal and hormonal function

Abstract: Thirteen patients with cirrhosis and tense ascites (six with and seven without peripheral edema) underwent 4- to 15-liter paracentesis without intravenous "colloid" replacement. Cardiac output increased from 6.6 +/- 0.7 liters per min at baseline to 8.2 +/- 0.7 liters per min (p less than 0.003) 1 hr after large-volume paracentesis completion and fell to 7.5 +/- 0.69 liters per min (p less than 0.05 vs. baseline, p less than 0.02 vs. 1 hr) 24 hr after large-volume paracentesis completion. There was no change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
3
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 16 publications
2
39
3
1
Order By: Relevance
“…A transient state of hypovolemia after large-volume paracentesis can be inferred also from the observation of raised levels of PRA and PAC in 11 patients. In almost all cases the raised PRA and PAC had reversed in a few days and were not correlated with an increased risk of recurrent ascites or 19). Therefore adequate expansion of plasma volume is essential to attenuate the hypovolemic effect of large-volume paracentesis.…”
Section: Discussionmentioning
confidence: 93%
“…A transient state of hypovolemia after large-volume paracentesis can be inferred also from the observation of raised levels of PRA and PAC in 11 patients. In almost all cases the raised PRA and PAC had reversed in a few days and were not correlated with an increased risk of recurrent ascites or 19). Therefore adequate expansion of plasma volume is essential to attenuate the hypovolemic effect of large-volume paracentesis.…”
Section: Discussionmentioning
confidence: 93%
“…Two recent studies (19,21) have found an increased plasma renin activity (suggesting a decrease in plasma volume) after large-volume paracentesis (8 and 13.2 liters in each study, respectively), but neither study actually measured plasma volume.…”
Section: Discussionmentioning
confidence: 95%
“…Paracentesis without albumin infusion was clearly associated with a reduction in effective blood flow and thought to account for the higher incidence of renal and electrolyte disorders occurring in these patients. The effects of therapeutic paracentesis without albumin infusion on cardiovascular and renal function are described by Simon et al (8) in this issue of Hepatology. Thirteen patients (6 with and 7 without peripheral edema) underwent large-volume paracentesis (4 to 15 liters) without intravenous albumin replacement.…”
Section: Paracentesis: a Safe And Effective Form Of Therapymentioning
confidence: 95%